Analysis of the UCSF Symptom Management Theory: Implications for Pediatric Oncology Nursing - Linder, Lauri (J Pediatr Oncol Nurs, 2010)
Symptom management research is a priority for both children and adults with cancer. The UCSF Symptom Management Theory (SMT) is a middle range theory depicting symptom management as a multidimensional process. A theory analysis using the process described by Walker and Avant evaluated the SMT with attention to application in research involving children with cancer. Application of the SMT in studies involving children has been limited to descriptive studies testing only portions of the theory. Findings of these studies have provided empiric support for the relationships proposed within the SMT. Considerations for future research involving children include attention to measurement of symptoms and clarity regarding the location of the parents and family within the model. With additional testing and refinement, the SMT has the potential to guide nursing research and practice to improve symptoms for children with cancer.